NIMG-05. DYNAMIC SUSCEPTIBILITY CONTRAST MRI IN THE EVALUATION OF BRAIN METASTASES: CURRENT PRACTICE REVIEW AND RATIONALE FOR STUDY OF BASELINE PERFUSION IMAGING PRIOR TO STEREOTACTIC RADIOSURGERY (STARBEAM-X). (14th November 2022) - Dobeson, Caroline; Birkbeck, Matthew; Bhatnagar, Priya; Hall, Julie; Pearson, Rachel; West, Serena; English, Philip; Butteriss, David; Lewis, Joanne
Abstract: Stereotactic radiosurgery (SRS) is an established focal treatment for brain metastases with high local control rates. An important side-effect of SRS is the development of radionecrosis. On conventional MR imaging, radionecrosis and tumour progression often have similar appearances, but have contrasting management approaches. Perfusion MR imaging is often used in the post-treatment setting in order to help distinguish between the two, but image interpretation can be fraught with challenges.Perfusion MR plays an established role in the baseline and post-treatment evaluation of primary brain tumours and a number of studies have concentrated on the value of perfusion imaging in brain metastases. Of the parameters generated, relative cerebral blood volume is the most widely used variable in terms of its clinical value in differentiating between radionecrosis and tumour progression.Although it has been suggested that the rCBV tends to be elevated in active metastatic disease following treatment with radiosurgery, but not with treatment-related changes, the literature available on interpretation of the ratios provided in the context of defining tumour progression is not consistent.We provide an overview of the role perfusion MRI plays in the assessment of brain metastases and introduces the rationale for the STARBEAM-X study (Study of assessment of radionecrosis in brain metastases using MR perfusion extra imaging), which will prospectively evaluate baseline perfusion imaging in brain metastases. We present here the results of the first three patients recruited to the feasibility phase of this study. We hope this study will allow insight into the vascular appearance of metastases from different primary sites, and aid in the interpretation of post-treatment perfusion imaging.